Secondary Metabolites Isolated from Chilean Marine Algae: A Review - Arrieche, Dioni; Carrasco, Hector; Olea, Andres F.; Espinoza, Luis; San Martin Barrientos, Aurelio Del Carmen; Taborga, Lautaro (My University, 2022)
Chile is in the extreme southwestern part of America, and it has an extreme length, of approximately 4300 km that increases to 8000 km considering the Chilean Antarctic Territory. Despite the large extent of its coastal territory and the diversity of geographic environments and climates associated with Chilean coasts, the research on marine resources in Chile has been rather scarce. From marine organisms found in Chilean coastal waters, algae have been the most studied, since they contain a wide range of interesting secondary metabolites that have some structural traits that make them unique and uncharacteristic. Thus, a wide structural variety of natural products including terpenoids (monoterpenes, sesquiterpenes, diterpenes, and meroterpenoids), furanones, and C-15-acetogenins have been isolated and identified. This review describes the existing literature on bioprospecting and exploration of secondary metabolites from Chilean coasts.
Keywords: marine natural products; secondary metabolites; chilean algae; biological activities; biosynthesis; structure elucidation